Genetic diversity of common bean genotypes as revealed by seed storage proteins and some agronomic traits - Marzooghian, Akbar; Moghaddam, Mohammad; Valizadeh, Mostafa; Kooshki, Mohammad Hasan (Plant Breeding and Seed Science, 2012)
Evaluation of the genetic diversity present within species is essential for conservation, management and utilization of the genetic resources. The objective of this study was to evaluate genetic variability of 70 com- mon bean genotypes for seed storage proteins, grain morphological characteristics and agronomic traits. Two methods of extracting soluble seed proteins in salt were used. Positive correlations were observed among both seed morphological characters and developmental charac- ters while yield components showed negative correlations with each other. Factor analysis for agronomic and grain morphological traits resulted in three factors were named yield components, seed morphology and phenology, respectively. Most genotypes had lower or medium scores for yield components and phenology factors. Considerable diversity was observed for seed morphology factor among the common bean genotypes. Nei’s diversity coefficient (He = 0.4), effective number of alleles (Ae = 1.69) and number of polymorphic loci (N = 17) indicated larger variation in the extraction method of soluble proteins in low salt (0.2 M NaCl) than high salt (1 M NaCl) condition. Considering that the centers of diversity for common bean are different in seed size, the result of GST statistics showed that bands with relative mobility of 30, 32, 38 and 40 differen- tiated two weight groups more than other bands. Furthermore, significant differences were observed between these bands for number of pods per plant and number of seeds per plant.